Clinical and laboratory predictors to differentiate severe dengue from scrub typhus in children - Elangovan, Bharathi; T., Rajesh N. (International Journal of Contemporary Pediatrics, 2019)
Background: Objective of study was to compare the clinical features and laboratory parameters at admission and differentiate severe dengue from scrub typhus in children. Methods: Retrospective analysis of case records and comparison of clinical and laboratory parameters at admission of all children with a diagnosis of severe dengue and scrub typhus was done. Results: A total of 72 children were included (severe dengue =40; scrub typhus =32) during the study period. The mean (SD) age of children with severe dengue and scrub typhus was 7.9(3.8) and 11.8(5.8) years, respectively. Majority of children with severe dengue presented with hypotension, 21(52.5%) vs 3(9.4%) in scrub typhus. Children with severe dengue had a relatively low ANC (2.6±1.97x103/mm3 vs 3.9±2.06x103/mm3), low platelet count (50.23±35.55x103/mm3 vs 140±95.0x103/mm3) and low mean ESR at 1hour (8.1±6.82mm vs 33.88±13.79mm) than scrub typhus. Conclusions: Compared to scrub typhus, severe dengue was significantly associated with hypotension, lower ANC, ESR and platelets.